Wood anatomy of species of a deciduous dry forest at Tamaulipas, Mexico - Ramírez-Martínez, Monserrat; Terrazas, Teresa; Aguilar-Rodríguez, Silvia; Martínez-Ávalos, José Guadalupe (Instituto de Ecología, A.C., 2017)
Wood anatomy of 21 species of the deciduous dry forest at Tamaulipas, Mexico was studied with the aim of contributing to their anatomical knowledge and to compare their attributes with each other and with other deciduous dry forest of Mexico. The results showed growth rings, and 52% of them have diffuse porosity. Fibers were libriform with thick walls in 43% species and very thick in Ebenopsis ebano, Drypetes lateriflora, Randia sp. and Vachellia farnesiana. Paratracheal parenchyma predominated and rays were heterocellular, except for five species of Fabaceae. The wood of the three species which is described for the first time is distinctive: Harpalyce arborescens by its storied axial and radial parenchyma, Ocotea tampicensis by its narrow vessels and short fibers and Robinsonella discolor by its fibrotracheids and silica bodies in rays. When comparing the species' wood anatomy with their taxonomic groups similarities within groups but differences in cells size were found. Quantitative wood values are within those registered for the deciduous dry forest reserve at Chamela. However, the length of vessel elements and fibers is shorter and the vessel diameter is narrower in the species studied here. The anatomy of both communities is related to the type of climate that allows them to survive during the dry season that occurs annually.